UPAYA PEMBINAAN MASYARAKAT DALAM RANGKA PENGEMBANGAN DESA EKOWISATA DI DUSUN MENDIRO, DESA PANGLUNGAN, KECAMATAN WONOSALAM, KABUPATEN JOMBANG - Satrya, I Dewa Gde; Kaihatu, Thomas Stefanus; Pranata, Lexi (Jurnal Terapan Abdimas, 2019)
Abstarct. The problems faced by the Mendiro village community are the function of protected forests, hunting of birds, timber theft / bamboo shoots, river pollution, logging in springs and the transfer of land ownership owned by people outside Wonosalam. The purpose of community service is to provide knowledge and skills to the hamlet of Mendiro Village and Panglungan Village to create a village of residence to become an ecotourism village. Over time, found collaboration of agro-tourism products which is the development of the potential that exists in the field. Service is carried out using participatory counseling methods followed by demonstrations and practices. The training activities are carried out intensively from February to August 2018 at the Panglungan Village Hall and at the residents' houses which are used as Tourist Information Centers. The activity begins with the provision of materials on the principles of ecotourism and community-based tourism, and is continued with comprehensive material to create an ecotourism village, starting with the provision of local culinary delights to making homestays. The conclusion of this dedication activity shows that the residents have high motivation to make their home village become an ecotourism village in order to overcome a number of problems listed above. Keywords: ecotourism, agro-tourism, community-based tourism  Abstrak. Masalah yang dihadapi masyarakat Desa Mendiro adalah fungsi hutan lindung, perburuan burung satwa, pencurian kayu/rebung, pencemaran sungai, penebangan di area mata air dan alih kepemilikan lahan milik orang di luar Wonosalam. Tujuan pengabdian kepada masyarakat adalah untuk memberi pengetahuan dan keterampilan kepada masyarakat Dusun Mendiro dan Desa Panglungan untuk menciptakan desa tempat tinggal menjadi desa ekowisata. Pengabdian dilakukan dengan menggunakan metode penyuluhan partisipatif yang diikuti dengan demonstrasi dan praktik. Kegiatan pelatihan dilaksanakan secara intensif sejak bulan Februari sampai Agustus 2018 bertempat di Balai Desa Panglungan dan di rumah warga yang dijadikan Tourist Information Centre. Kegiatan diawali dengan pemberian materi tentang prinsip-prinsip ekowisata dan pariwisata berbasis masyarakat, dan dilanjutkan dengan materi yang komprehensif untuk menciptakan desa ekowisata, mulai penyediaan kuliner lokal hingga pembuatan homestay. Kesimpulan dari kegiatan pengabdian ini menunjukkan bahwa para warga memiliki motivasi yang tinggi untuk menjadikan desa tempat tinggal mereka menjadi desa ekowisata guna mengatasi sejumlah permasalahan yang tertera di atas. Kata kunci: Ekowisata, Pariwisata Berbasis Masyarakat